Strategy, leadership, and AI in the cyber ecosystem : the role of digital societies in information governance and decision making - Jahankhani, Hamid (Academic Press, 2021)
Strategy, Leadership and AI in the Cyber Ecosystem investigates the restructuring of the way cybersecurity and business leaders engage with the emerging digital revolution towards the development of strategic management, with the aid of AI, and in the context of growing cyber-physical interactions (human/machine co-working relationships). The book explores all aspects of strategic leadership within a digital context. It investigates the interactions from both the firm/organization strategy perspective, including cross-functional actors/stakeholders who are operating within the organization and the various characteristics of operating in a cyber-secure ecosystem. As consumption and reliance by business on the use of vast amounts of data in operations increase, demand for more data governance to minimize the issues of bias, trust, privacy and security may be necessary. The role of management is changing dramatically, with the challenges of Industry 4.0 and the digital revolution. With this intelligence explosion, the influence of artificial intelligence technology and the key themes of machine learning, big data, and digital twin are evolving and creating the need for cyber-physical management professionals. Discusses the foundations of digital societies in information governance and decision-making Explores the role of digital business strategies to deal with big data management, governance and digital footprints Considers advances and challenges in ethical management with data privacy and transparency Investigates the cyber-physical project management professional [Digital Twin] and the role of Holographic technology in corporate decision-making.